2014
DOI: 10.1188/14.cjon.e58-e63
|View full text |Cite
|
Sign up to set email alerts
|

Decision Making After <i>BRCA</i> Genetic Testing

Abstract: The purpose of this study was to evaluate women who have completed hereditary cancer risk assessment and BRCA genetic testing to determine if they considered themselves prepared to proceed with decision making regarding cancer screening and prevention options. Levels of decisional conflict were explored, as was their preference for information delivery. The prospective, descriptive survey was conducted at a breast and clinical genetics clinic at a comprehensive cancer center in the northeastern United States. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 19 publications
2
6
1
Order By: Relevance
“…Those who expressed difficulty with risk-management decision-making often discussed negative emotions related to the risk-management decisionmaking process as well. Our results support findings that unaffected individuals feel less prepared to make a decision regarding cancer risk management and have more decisional conflict than individuals with a personal history of cancer (Connors et al 2014) and that younger individuals with a BRCA mutation are more likely to report more need for additional support after learning about the mutation (Metcalfe et al 2000). However, unlike the Connors etal.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Those who expressed difficulty with risk-management decision-making often discussed negative emotions related to the risk-management decisionmaking process as well. Our results support findings that unaffected individuals feel less prepared to make a decision regarding cancer risk management and have more decisional conflict than individuals with a personal history of cancer (Connors et al 2014) and that younger individuals with a BRCA mutation are more likely to report more need for additional support after learning about the mutation (Metcalfe et al 2000). However, unlike the Connors etal.…”
Section: Discussionsupporting
confidence: 84%
“…In contrast with physicians, participants generally described genetic counselors as being involved short term in the decision-making process by providing information and recommendations. While research has shown that women who received a genetics consultation for HBOC felt more prepared to make management decisions and had low decisional conflict after pre-test counseling and results disclosure (Connors et al 2014), information from genetic counseling sessions can also be helpful in surgical decision-making (Ray et al 2005). However, the role of the genetic counselor is not just to provide information, but to also provide psychosocial counseling to patients (Resta et al 2006).…”
Section: Discussionmentioning
confidence: 99%
“…34 Approximately two-thirds (67.4%) of the participants in this study who received the PDA were well prepared to make screening decisions as a result of viewing the PDA compared with approximately one-half (48.2%) of the participants who received the EDU, a finding that is similar to or exceeds data from other studies of PDAs. [35][36][37][38] Similarly, 50.0% to 68.0% of the PDA participants had low decisional conflict about their screening choice, which was approximately 20 percentage points better than that for participants who received the EDU. The magnitude of the differences between the 2 groups on the Decisional Conflict Scale Informed and Values Clarity subscales also exceeded the difference reported in the most recent Cochrane Systematic Review 27 for PDAs delivered in preparation for a consultation with a health care clinician.…”
Section: Discussionmentioning
confidence: 96%
“…For women with access to them, genetic counselors provide more thorough information about risk and prevention than generalist physicians or oncologists, combined with support to process information and make decisions [152]. Although the health information they provide can also vary [153], these interactions are associated with higher uptake of risk reduction methods [154].…”
Section: Women’s Prevention Decision Makingmentioning
confidence: 99%